Economic and financial sustainability of an Acacia decurrens-based Taungya system for farmers in the Upper Blue Nile Basin, Ethiopia. (January 2020) - Nigussie, Zerihun; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Adgo, Enyew; Tsubo, Mitsuru; Ayalew, Zemen; Abele, Steffen
Highlights: This paper examined the financial viability of farmers' investment in acacia plantations in the Upper Blue Nile Basin. The acacia-based taungya system has the potential to serve as an important developmental pathway out of poverty in Ethiopia. In an Acacia-based plantation system, well endowed farmers are benefiting more compared to resource-poor counterparts. In the early sales of plantation stands, in the first two years, the stand buyers got more returns than the growers. Abstract: The use of tree-based fallowing as a sustainable land management system may serve as an important developmental pathway out of poverty across drought-prone watersheds in the Upper Blue Nile Basin, Ethiopia. This study employs a financial analysis technique, the computation of net present values, to explore the ﬁnancial viability of farmers' investments in an intercropping farming system known as taungya . The analysis employs scenarios that include different farming systems, such as A. decurrens (J.C. Wendl.) Willd. cum teff ( Eragrostis tef ) intercropping, A. decurrens monocropping, and teff monocropping, as well as changes in output (charcoal and teff) prices and the discount rate. In addition, the time of sale is evaluated in terms of the distribution of profits between buyers and sellers and between sharecroppers and landowners. The intercropping practice ( A. decurrens cum teff in the first year) tended to be more profitable than the alternative systems. Financially constrained farmers who have to sell their stands early, however, forego gains. Profits from stand sales later in the 5-year evaluation period were more equally shared between sellers and buyers. Sharecropping profits for farmers ranked among the lowest of the computed profits. A sensitivity analysis revealed that an increase in the discount rate tends to have a more detrimental effect than price fluctuations on the proﬁtability of acacia-based taungya systems, although sharp price fluctuations could affect profitability and cause a farmer to shift back to an annual crop system. Despite their higher profitability, tree-based systems impose a risk of liquidity bottlenecks on farmers throughout the 5-year investment period, which implies that those who are endowed with land or who are more financially well-off can benefit from the required 5-year investment, but it may be more difficult for those who lack land or the necessary financial resources. Providing affordable financing for poorer and landless farmers could increase farmers' use of the taungya system and allow a more equitable distribution of benefits among the rural population.